Direct Memory Loading Of An Operating System Through Preboot Execution In A Homogenous Computing Environment - Nair, Remesh Seth (2009)
This research will analyze the bootloading process used in different remote boot solutions and propose steps that can be used to reduce the different stages in a remote boot solution by using Preboot Execution Environment (PXE)